Deficits in sequential processing manifest in motor and linguistic tasks in a multigenerational family with childhood apraxia of speech. - Peter, Beate; Button, Le; Stoel-Gammon, Carol; Chapman, Kathy; Raskind, Wendy H. (Clinical Linguistics & Phonetics, 2013)
The purpose of this study was to evaluate a global deficit in sequential processing as candidate endophenotypein a family with familial childhood apraxia of speech (CAS). Of 10 adults and 13 children in a three-generational family with speech sound disorder (SSD) consistent with CAS, 3 adults and 6 children had past or present SSD diagnoses. Two preschoolers with unremediated CAS showed a high number of sequencing errors during single-word production. Performance on tasks with high sequential processing loads differentiated between the affected and unaffected family members, whereas there were no group differences in tasks with low processing loads. Adults with a history of SSD produced more sequencing errors during nonword and multisyllabic real word imitation, compared to those without such a history. Results are consistent with a global deficit in sequential processing that influences speech development as well as cognitive and linguistic processing.